Diseases of the liver and biliary system in children - Kelly, Deirdre A.; Wiley InterScience (Online service) (Chichester, UK ; Hoboken, NJ : Wiley-Blackwell, 2008)
'An excellent up-to-date comprehensive and practical text book dealing with all aspects of paediatric hepatobiliary disease. It will be useful to both generalists and specialists as it is clinically focused with a problem-solving approach and should be useful for day-to-day as well as more esoteric clinical problems. I found it useful in my general paediatric practice and my trainees have also found it useful. It is very practical with a diagnostic approach and lots of tables and clinical pathways to follow when confronted with day-to-day clinical problems. I have road-tested it in real life w.
Diseases of the Liver and Biliary System in Children; Contents; Contributors; Foreword to the First Edition; Preface; Part 1 Structure Function, and Repair; 1 Structure Function and Repair of the Liver; Part 2 Investigating the Liver; 2 The Approach to the Child with Liver Disease: Differential Diagnosis and Useful Investigations; Part 3 Liver Disease in Pregnancy; 3 The Effects of Liver Disease on Mother and Child; Part 4 Neonatal liver disease; 4 The Jaundiced Baby; 5 The Acutely Ill Baby; Part 5 Acute Liver Disease; 6 Infective Disorders of the Liver; 7 Acute Liver Failure.
Includes bibliographical references and index.
Print version record.
Keywords: Liver -- Diseases; Biliary tract -- Diseases; Pediatric gastroenterology; Liver diseases; Child; Infant; Pediatric gastroenterology; Electronic books